2011
DOI: 10.1007/s10461-011-9985-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Characteristics and Behavioral Risk Factors of Female Sex Workers in Sub-Saharan Africa: A Systematic Review

Abstract: Sex work remains an important contributor to HIV transmission within early, advanced and regressing epidemics in sub-Saharan Africa, but its social and behavioral underpinnings remain poorly understood, limiting the impact of HIV prevention initiatives. This article systematically reviews the socio-demographics of female sex workers (FSW) in this region, their occupational contexts and key behavioral risk factors for HIV. In total 128 relevant articles were reviewed following a search of Medline, Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
268
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(291 citation statements)
references
References 107 publications
(197 reference statements)
20
268
3
Order By: Relevance
“…However, consistent condom use among FSWs and truckers is low 14 , and this is largely explained by economic and relationship factors including poverty, refusal by male partners to use condoms, alcohol use before sex and beliefs that condoms kill the mood for sex. These barriers continue to hamper effective use of condoms for HIV prevention, and explain why, despite high levels of knowledge of condom use as an HIV prevention strategy, both FSWs and truckers continue to engage in unprotected sex 21 . Previous studies have identified a number of factors that affect condom use among female sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…However, consistent condom use among FSWs and truckers is low 14 , and this is largely explained by economic and relationship factors including poverty, refusal by male partners to use condoms, alcohol use before sex and beliefs that condoms kill the mood for sex. These barriers continue to hamper effective use of condoms for HIV prevention, and explain why, despite high levels of knowledge of condom use as an HIV prevention strategy, both FSWs and truckers continue to engage in unprotected sex 21 . Previous studies have identified a number of factors that affect condom use among female sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…In Kampala, recent research has noted high HIV prevalence among women in the general population (Nakku-Joloba et al, 2015), and specifically among women engaged in sex work and their clients (Lindan et al, 2015;Vandepitte et al, 2011). Female sex workers are vulnerable to infection because many have multiple concurrent partners, may not always be able to negotiate condom use, and may also be at risk of violence from clients and regular partners, among other factors (Rutakumwa, Mbonye, Kiwanuka, Bagiire, & Seeley, 2015;Schulkind, Mbonye, Watts, & Seeley, in press;Scorgie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In such settings female sex workers (FSW) and their clients are at greater risk of HIV and other sexually transmitted infections than the general population (Baral et al, 2012;Scorgie et al, 2012), due largely to inconsistent condom use with multiple sexual partners, including with the regular partners (Rekart, 2006;Vanwesenbeeck, 2001;Wojcicki & Malala, 2001). Reaching sex workers and their clients can therefore significantly contribute to global efforts to fast track HIV prevention and treatment (UNAIDS, 2014).…”
Section: Introductionmentioning
confidence: 99%